Penerapan Ketentuan Kepailitan Terhadap Bank yang Bermasalah - Feri Pramudya Suhartanto; Muhamad Fadly Darmawan; Noval Febriansyah; Zahra Febriani Nugraha; Hany Fauziyyah Irawan; Farahdinny Siswajanthy (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This study explores the implementation of bankruptcy provisions for troubled banks. The aim is to analyze the legal and economic impacts of bankruptcy processes on banks facing financial difficulties. The research methodology involves legal studies and economic analyses of bankruptcy cases involving banks. The results underscore the importance of appropriately implementing bankruptcy provisions to efficiently and effectively address troubled banks. Findings indicate that failure to implement adequate bankruptcy provisions can have serious consequences for financial system stability. The study emphasizes the need for clear policies and efficient mechanisms to address financially troubled banks to maintain overall financial system stability. The implications of this research provide guidance for regulators and legal practitioners in developing policies related to handling financially troubled banks. In conclusion, the study highlights the necessity of clear policies and efficient mechanisms in addressing financially troubled banks to maintain overall financial system stability.